2020
DOI: 10.22456/1679-9216.100679
|View full text |Cite
|
Sign up to set email alerts
|

Metamizol and Scopolamine for Conventional or Two-Port Laparoscopic-Assisted Ovariohysterectomy in Dogs

Abstract: Background: Ovariohysterectomy (OVH) is one of the most appliedtechniques in Veterinary Medicine. Although some analgesic protocols are used after this procedure in order to control post operatory pain, there is a lack of knowledge of the efficacy after conventional and two port laparoscopic-assisted techniques in dog female. Although the combined formulation of metamizol and scopolamine is used, there is no knowledge about the efficacy and collateral effects in a 6 h regimen after OVH. The aim of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Another study conducted by Deneuche et al (2004) demonstrated the efficacy of pre and peri-operative administration of meloxicam or ketoprofen in analgesia after orthopedic surgeries in the first 24 hours. Dipyrone has already been tested and proved to be effective in the postoperative analgesia of dogs undergoing several procedures such as open and video assisted ovariohysterectomy (Imagawa et al 2011, Kalchofner Guerrero et al 2015, Dalmolin et al 2020, and total hip replacement (Rudolff 2011). Similar favorable results have already been found in the human medicine literature (Hearn et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Deneuche et al (2004) demonstrated the efficacy of pre and peri-operative administration of meloxicam or ketoprofen in analgesia after orthopedic surgeries in the first 24 hours. Dipyrone has already been tested and proved to be effective in the postoperative analgesia of dogs undergoing several procedures such as open and video assisted ovariohysterectomy (Imagawa et al 2011, Kalchofner Guerrero et al 2015, Dalmolin et al 2020, and total hip replacement (Rudolff 2011). Similar favorable results have already been found in the human medicine literature (Hearn et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The potent analgesic effect of dipyrone in dogs is well-known and it is mainly related to the inhibition of the cyclooxygenase (COX) enzyme, and consequent decrease in prostaglandin synthesis, resulting in the reduced sensitivity of nerve endings to inflammatory mediators such as bradykinin. Several studies have found that dipyrone is effective as an analgesic in postoperative pain in dogs undergoing removal of tumors, ovarian hysterectomy, and splenic torsion (Caulkett et al, 2003;Imagawa et al, 2011;Zanuzzo et al, 2015;Guerrero et al, 2015;Bellio et al, 2015;Souza et al, 2016;Ortiz et al, 2016;Ferrigno et al, 2016;Sembenelli et al, 2016;Dalmolin et al, 2020). For Ripplinger et al (2018), the association of metamizole and morphine or metamizole and methadone did not result in an increase in adverse effects in dogs when compared to animals treated with morphine or methadone alone.…”
Section: Analgesic Effectmentioning
confidence: 99%